Potent anti‐tumor response by targeting B cell maturation antigen (BCMA) in a mouse model of multiple myeloma. Issue 7 (31st March 2015) - Oden, Felix; Marino, Stephen F.; Brand, Janko; Scheu, Susanne; Kriegel, Cathleen; Olal, Daniel; Takvorian, Anna; Westermann, Jörg; Yilmaz, Buket; Hinz, Michael; Daumke, Oliver; Höpken, Uta E.; et al.
Abstract : Multiple myeloma (MM) is an aggressive incurable plasma cell malignancy with a median life expectancy of less than seven years. Antibody‐based therapies have demonstrated substantial clinical benefit for patients with hematological malignancies, particular in B cell Non‐Hodgkin's lymphoma. The lack of immunotherapies specifically targeting MM cells led us to develop a human‐mouse chimeric antibody directed against the B cell maturation antigen (BCMA), which is almost exclusively expressed on plasma cells and multiple myeloma cells. The high affinity antibody blocks the binding of the native ligands APRIL and BAFF to BCMA. This finding is rationalized by the high resolution crystal structure of the Fab fragment in complex with the extracellular domain of BCMA. Most importantly, the antibody effectively depletes MM cells in vitro and in vivo and substantially prolongs tumor‐free survival under therapeutic conditions in a xenograft mouse model. A BCMA‐antibody‐based therapy is therefore a promising option for the effective treatment of multiple myeloma and autoimmune diseases. Highlights: A high affinity monoclonal antibody directed against the B cell maturation antigen. The antibody binds to the ligand‐binding site of BCMA and blocks APRIL and BAFF. The BCMA‐antibody depletes multiple myeloma cells in vitro through ADCC and CDC. The BCMA‐antibody prevents tumor growth in mouse models of multiple myeloma.